Photo-Induced Aerobic Oxidation of C–H Bonds - Haolin Chen; Feng Liu (Molecules)
The photo-induced aerobic oxidation of C–H bonds has become an increasingly valuable strategy in organic synthesis, offering a green and efficient method for introducing oxygen into organic molecules. The utilization of molecular oxygen as an oxidant, coupled with visible-light photocatalysis, has gained significant attention due to its sustainability, atom economy, and environmentally benign nature. This review highlights the recent advancements in the field, focusing on the development of metal-free and transition-metal-based photocatalytic systems and novel photosensitizers capable of promoting selective C–H bond oxidation. The mechanistic pathways involved in various substrate oxidations, including benzylic, alkyl, alkene, and alkyne C–H bond transformations, are discussed. This review concludes with insights into the potential for integrating photocatalysis with renewable energy sources, positioning photo-induced aerobic oxidation as a cornerstone of sustainable chemical processes.